TAUTAN KONTEKS SITUASI DAN KONTEKS BUDAYA: KAJIAN LINGUISTIK SISTEMIK FUNGSIONAL PADA CERITA TERJEMAHAN FIKSI ”HALILIAN” - Rosmawaty Rosmawaty (LITERA, 2011)
Halilian is a prose or story presented in a relaxing situation or leisure time. The Angkola community’s social reality, local wisdom, socio-cultural values, and ideology reflected in the Halilian text can be revealed through a systemic functionallinguistics study. This study tries to reveal the social construction, comprising men’sand women’s positions and roles in society. Human relations and life nuances due to the relations vary, depending on the problems that each actor encounters. Human beings have problems related to family and society. The findings show that in the Angkola culture: (1) it is necessary to pay a visit to parents wherever one lives because this has effects on life, (2) one must keep promise, (3) there is still a belief in spirits, and (4) the husband-wife interaction is a one way interaction, with the husband’s power being stronger than the wife’s.